The Spectator, 2001-10-18 - Spectator, Valdosta State University (Valdosta State University, 2001)
The Spectator. October 18, 2001. Vol 69. No. 9. (Valdosta State University, Georgia) Sprinklers Jam Wet Sidewalk -- All Hail Queen Holly Blount -- TKE Under Investigation -- Minutes Called into Question.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete, rendered incorrectly, or different from final print editions. Some fonts have been changed. Processed by Dallas Suttles at Valdosta State University Archives and Special Collections, 2016. dasuttles@valdosta.edu.
Keywords: Valdosta State University -- Periodicals